Characterization of Soil Conditions for Wild Edible Plants’ Habitats in Semi-Arid Areas of Uganda - Kyakuwaire, M.; Ochwoh, V.; Kakudidi, E.; Tumuhairwe, J. (IJAIR, 2015)
Wild edible plants are known to supplement farm crops in rural African households, especially during famine periods. In Uganda, conservation of such plants is at stake. Their habitats are continuously being degraded or converted to other land uses. Assessment of soils on agriculture land is common, but limited for wild edible plants’ habitats. A study was done to characterize and compare soil physical and chemical properties of wild edible plants’ habitats and farmers’ gardens for the purpose of assessing the potential for cultivation of the plants on the gardens. Soils 0-20 cm and 30-50 cm deep were randomly sampled from the rhizosphere of the selected plants and from gardens of farmers. Soil samples were analyzed using published standard procedures. Fisher’s test was used to compare the soil conditions of the wild edible plants’ habitats for homogeneity, Pearson’s correlation coefficient to find association between the plants occurrence and their habitats soil conditions, and ANOVA to establish differences between the soil properties of the wild edible plants’ habitats and farmers’ gardens. The soil physical and chemical conditions of the different habitats where the wild edible plants naturally grow were similar (p>0.05), highly associated with the plants’ occurrence(r>0.5) and significantly more fertile (p<0.05) than farmers’ gardens. On-farm establishment of the wild edible plants could require soil amendment.
Keywords: Conservation; Food Plants; Spontaneously Growing; On-Farm; Soil Properties